TINGKAT KESIAPAN RENCANA TANGGAP DARURAT PELAKU UMKM KULINER DI KELURAHAN SRENGSENG SAWAH - Meisi Riana; Antinah Latif; Elviana; Dimas Bayu Pinandoyo, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Fire is a work accident that has a wide impact on losses, from facilities to fatalities. Activities in food processing are one of the activities that have the potential to be fire hazardous. It is important to know the level of emergency response plans as an indicator of the preparedness of Culinary MSME actors against potential fire disasters. The aim of the research is to determine the level of preparedness for emergency response plans in Culinary MSMEs. The research method was cross-sectional with a sample size of 87 Culinary MSMEs in the Srengseng Sawah Subdistrict area. The questionnaire used has been tested for validity using the calculated r>r table and reliability with a Cronbach's Alpha number of 0.823. Based on these results, the questionnaire is valid and reliable to use. It is known that the characteristics of respondents for male gender have a greater number, namely 52.9%, for age the largest percentage is 35.6% of respondents aged 26-35 years, and half of the number of respondents or as many as 58.6% of respondents have Last level of education is Senior High School (SMA). As many as 89.7% of respondents had never participated in training, especially fire disaster mitigation training. The results showed that the level of emergency response plan readiness was at the highest percentage, namely 45.5% of respondents had emergency response plan readiness at the less ready level.